Attitudes, barriers and facilitators of hospital pharmacists conducting practice‐based research: a systematic review. (21st June 2021) - Reali, Savannah; Lee, Teresa; Bishop, Jaclyn; Mirkov, Sanja; Johnson, Jacinta; McCourt, Elizabeth; Hughes, Jeffery; Pont, Lisa; Page, Amy Theresa; Penm, Jonathan
Abstract: Introduction: Practice‐based research is essential in enhancing medication knowledge, quality use of medicines, the scope of the pharmacy profession and improving patient outcomes. This systematic review aims to uncover the attitudes of hospital pharmacists towards practice‐based research and their perceptions of the barriers and facilitators to undertaking practice‐based research. Methods: A systematic search of MEDLINE, Embase, International Pharmaceutical Abstracts and Cumulative Index to Nursing and Allied Health Literature databases from 1 January 2000 to 11 March 2021 was conducted. Peer‐reviewed empirical studies exploring hospital pharmacists' perceptions of – as well as barriers and facilitators to – practice‐based research were included and a descriptive synthesis used to identify common themes. Results: Nine studies were included in this review. Barriers and facilitators across four broad themes were related to pharmacist capacity and capability, workplace environment, research resources, and research culture. Hospital pharmacists had a high interest in conducting research, but limited research experience. Common barriers identified were lack of time, workplace support, funding, research culture, and competing priorities. Having a post‐graduate qualification and a positive attitude towards research facilitated research participation. Departmental support, designated research time and creation of research networks and forums were seen as facilitators for practice‐based research. Conclusion: Hospital pharmacists recognise the importance of practice‐based research in improving knowledge, patient care and advancing pharmacy practice. However, large variation has been reported for their confidence and experience in practice‐based research. Building research capacity and capability by supporting post‐graduate research qualification, providing designated time and creating research networks may strengthen the research culture amongst hospital pharmacists.